(untitled) (Hoboken, NJ, 2006)
This book provides an introduction to the rapidly advancing and expanding field of fiber optic sensors, with chapters contributed by internationally recognized experts. Each of the three sections-Basic Components, Technology, and Applications-offers a stand-alone primer on a key area of the field. Together, they give engineers, scientists, graduate students, and advanced undergraduates a comprehensive resource on fiber optic sensors.
Keywords: Fiber optics,Optical fiber detectors,Sợi quang học